2016
DOI: 10.21037/tau.2016.02.03
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor promotes nerve regeneration by activating the JAK/STAT pathway in Schwann cells

Abstract: BackgroundRadical prostatectomy (RP) carries the risk of erectile dysfunction (ED) due to cavernous nerve (CN) injury. Schwann cells are essential for the maintenance of integrity and function of peripheral nerves such as the CNs. We hypothesize that brain-derived neurotrophic factor (BDNF) activates the Janus kinase (JAK)/(signal transducer and activator of transcription) STAT pathway in Schwann cells, not in neuronal axonal fibers, with the resultant secretion of cytokines from Schwann cells to facilitate ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 29 publications
0
29
0
2
Order By: Relevance
“…Some of the growth factors that have been widely used in the peripheral nerve regeneration include NGF (Jafari, Delaviz, Torabi, Mohammadi & Gheitasi, ), GDNF (Marquardt, ), CNTF (Xu, Chen, Lu, & He, ), BDNF (Lin, Zhang, et al (), neurotrophin 3 (Sterne, Coulton, Brown, Green, & Terenghi, ), VEGF (Mohammadi, Ahsan, Masoumi, & Amini, ), insulin‐like growth factor 1 (Sebben, Lichtenfels, & da Silva, ), leukemia inhibitory factor (Razavi et al, ), glial growth factor (Terenghi, ), platelet‐derived growth factor, and fibroblast growth factor 1 (Küçük et al, ). Many studies have shown that various types of vitamins such as vitamin B complex, vitamin B12 (Altun & Kurutas, ), vitamin E (Elsy, Khan, & Maheshwari, ), vitamin D3 (Chabas et al, ), vitamin D2 (Chabas et al, ), and vitamin C (Gess, Rohr, & Young, ) are effective in nerve regeneration.…”
Section: Other Factors For Nerve Regenerationmentioning
confidence: 99%
“…Some of the growth factors that have been widely used in the peripheral nerve regeneration include NGF (Jafari, Delaviz, Torabi, Mohammadi & Gheitasi, ), GDNF (Marquardt, ), CNTF (Xu, Chen, Lu, & He, ), BDNF (Lin, Zhang, et al (), neurotrophin 3 (Sterne, Coulton, Brown, Green, & Terenghi, ), VEGF (Mohammadi, Ahsan, Masoumi, & Amini, ), insulin‐like growth factor 1 (Sebben, Lichtenfels, & da Silva, ), leukemia inhibitory factor (Razavi et al, ), glial growth factor (Terenghi, ), platelet‐derived growth factor, and fibroblast growth factor 1 (Küçük et al, ). Many studies have shown that various types of vitamins such as vitamin B complex, vitamin B12 (Altun & Kurutas, ), vitamin E (Elsy, Khan, & Maheshwari, ), vitamin D3 (Chabas et al, ), vitamin D2 (Chabas et al, ), and vitamin C (Gess, Rohr, & Young, ) are effective in nerve regeneration.…”
Section: Other Factors For Nerve Regenerationmentioning
confidence: 99%
“…10 ). The effect of BDNF and VEGF in peripheral nerve injuries has been shown previously 49 , 50 ; these factors may play important roles in introducing host blood vessels and Schwann cells during peripheral nerve recovery. These indirect contributions to recovery suggested that the LT-NCLCs create an optimal niche for peripheral nerve regeneration.…”
Section: Discussionmentioning
confidence: 70%
“…Again, we co‐administered 24 nM of GNF5837 to determine if any factor acting through the Trk receptors played a role in altering length of the extensions. It has been reported that BDNF, acting through TrkB, is capable of activating STAT3, which is essential in axon extension . However, the addition of the pharmacological blocker did not result in a difference in neurite extension lengths (Fig.…”
Section: Resultsmentioning
confidence: 85%